Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL): a good practice guide, pictorial review, and new perspectives. Issue 2 (February 2022) - Mehdi, A.S.; Bitar, G.; Sharma, R.K.; Iyengar, S.; El-Sharkawi, D.; Tasoulis, M.K.; Attygalle, A.D.; Cunningham, D.; Sharma, B.; ,
Abstract : Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare but emerging T-cell non-Hodgkin lymphoma. It has two distinct subtypes, "effusion-only" or "mass-forming" disease, arising around implants in patients with in situ or previous history of textured-surface breast implants. The clinical, histopathological and imaging features are unique and nuanced as compared to primary breast malignancy and other lymphoma categories. Prompt recognition and diagnosis triggers referral to appropriate BIA-ALCL centres and initiation of treatment, with potential for excellent prognosis. Definitive management of both subtypes involves implant and capsule removal; systemic therapy is reserved for mass-forming disease and advanced-stage disease. There have been recent crucial advances in the diagnostic pathway, with publication of national and international guidelines: from the UK Medicines Healthcare products Regulatory Agency (MHRA) Plastic, Reconstructive and Aesthetic Surgery Expert Advisory Group (PRASEAG), and the United States National Comprehensive Cancer Network (NCCN). This review provides a practical guide to the clinical work-up of BIA-ALCL, enabling optimisation of the diagnostic imaging pathway, with representative cases.